Micromorphological differentiation of left and right stridulatory apparatus in crickets (Orthoptera: Gryllidae) - Li, Xiaoqiang; Zhang, Xue; Luo, Wenqi; Wang, Yinliang; Ren, Bingzhong (Zootaxa, 2016)
The present study compared micromorphological differentiation of stridulatory apparatus between the functional right tegmen and non-functional left tegmen, analyzed under scanning electron microscope (SEM), among eight Gryllidae species. The results showed that the main differences were found on the length and shape of files and teeth. The length of stridulatory file and teeth number were lower on the left stridulatory apparatus than that on right stridulatory apparatus in all species. However, the ratio between the length of stridulatory teeth and the interval of stridulatory teeth was significantly higher on the left stridulatory apparatus than that on right stridulatory apparatus in Dianemobius fascipes, Polionemobius taprobanensis, Pteronemobius gifuensis, Teleogryllus occipitalis and Oecanthus longicauda. In addition, the length of stridulatory teeth was positively related to number of stridulatory teeth, however, the interval of stridulatory teeth was negatively related to the ratio between the length of stridulatory teeth and the interval of stridulatory teeth for left and right stridulatory apparatus. Our result illustrated that the length of left and right stridulatory file and teeth length could be an effective character to distinguish species. Left stridulatory apparatus was not entirely degraded than right stridulatory apparatus.